The society : a novel - Winn, Karen (Dutton, an imprint of Penguin Random House LLC, 2026)
"Rumors about the Knox and its influence have swirled through Boston for centuries. While some believe the secret society is merely an elite social club, others are convinced it hides something more sinister... Vivian Lawrence was born into old-money Boston, but when her family fortune vanishes so does her carefully curated life. Desperate, she turns to an old family legend that ties her to the Knox and its inheritance, seeking a way into the exclusive secret society. She doesn't expect that entry to come in the form of Peter, a Knox insider with movie star good looks and just enough roughness to his charm to make Vivian weak in the knees for the first time in her life. Far from Boston's glittering elite is newcomer Taylor Adams, a young nurse eager to leave her humble past behind. When the effortlessly glamorous Vivian lands in her ER after a suspicious fall, Taylor is instantly captivated. But then Vivian abruptly disappears without a trace, sending Taylor on a search for answers that pulls her into the Knox itself--as their new employee. The further Taylor ventures into the Knox's world of unimaginable wealth and dark history, the more the mystery surrounding Vivian deepens. As Taylor will soon discover, more so than money or status, secrets are this society's true currency."--